Manipulating task constraints in small-sided soccer games: performance analysis and practical implications - Almeida, C. H.; Ferreira, A. P.; Volossovitch, A. (The Open Sports Sciences Journal, 2012)
Since an awareness of key task constraints can be extremely beneficial for coaches, the lack of scientific background about the effects of altered game rules/conditions on individual or team performances during soccer practice is surprising. The aim of the present study was to analyze the influence of different small-sided game (SSG) playing rules ("free-form", "two touches" and "four passes to score") on the offensive performance of young soccer players. Eight U-13 male soccer players were divided into two balanced teams. The experimental protocol consisted of three testing sessions separated by one-week intervals. In each session, teams faced each other in the three SSG conditions (3vs.3+goalkeepers) during periods of ten minutes interspersed with five minutes of passive recovery. Simple (i.e. Duration of ball possession, Players involved, Ball Touches, Passes, Shots, and Result of the Offensive Sequence) and composite (i.e. Players involved/ Duration, Ball Touches/Duration, Passes/Duration, Ball Touches/Players involved, Passes/Players involved, Passes/Ball Touches, and Goal/Shots) performance indicators were used to characterize the offensive performance of both teams. Results revealed that the factor "playing rule" had a significant effect on simple and composite indicators (p<0.05). It was concluded that manipulating task constraints, such as game rules, can direct practitioners towards intended behaviors, and consequently promote skill acquisition and improve performance in youth soccer. Further research is needed to extend the knowledge about the modification of playing rules in team sports practice.